(untitled) (Ágora Journal, 2020)
In the regency’s period, the gatherings in the city-Court were considered as suspect and dangerous meetings: the collective practices were object to criminalization. It is no coincidence that the street manifestations – including electoral events and sociopolitical protests – were considered as potentially riotous. On the account of the crime reports registered by the Police of the court and the Instruments of Justice Department, we intended to investigate the concrete actions of the individuals that took part on these gatherings in town and also the actions of the repressive devices of the State institutions. In this sense, we notice that the authorities in Court, besides fighting offences, acted preventively towards collective practices, viewed as unruly and turbulent. That way, the purpose of this work is to identify the gatherings that were treated as or effectively considered as illicit gatherings.